Optimizing Cocoa Productivity Through Soil Health and Microbiome Enhancement: Insights from Organic Amendments and a Locally Derived Biofertilizer - Jennifer E. Schmidt; Julia Flores; Luigy Barragan; Freddy Amores; Sat Darshan S. Khalsa (Microorganisms, 2025)
Despite growing interest in improving soil health on cocoa farms, applied research on the impacts of specific amendments on soil and plant outcomes is lacking. An integrated assessment of the impacts of two different organic amendments (compost and vermicompost) and a microbial biofertilizer on soil physical, chemical, and biological properties, as well as cocoa flowering, fruit set, and yield, was conducted in Guayaquil, Ecuador. Complementary culture-dependent and culture-independent methods were used to assess the impacts of amendments on microbial diversity, community composition, and specific taxa. Compost or vermicompost application affected soil chemical properties, including potassium, phosphorus, and sodium, and had small but significant effects on fungal beta diversity. Biofertilizer application slightly lowered soil pH and altered the total abundance of specific taxonomic groups including Azotobacter sp. and Trichoderma sp., with borderline significant effects on Azospirillum sp., Lactobacillus sp., Pseudomonas sp., calcium-solubilizing bacteria, and phosphorus-solubilizing bacteria. Amplicon sequencing (16S, ITS) identified 15 prokaryotic and 68 fungal taxa whose relative abundance was influenced by organic amendments or biofertilizer. Biofertilizer application increased cherelle formation by 19% and monthly harvestable pod counts by 11% despite no impact on flowering index or annual pod totals. This study highlights the tangible potential of microbiome optimization to simultaneously improve on-farm yield and achieve soil health goals on cocoa farms.